The Influence of Innovation Culture and Organizational Support on Employee Performance in Fostering Innovative Behavior within the X Department of West Java Province - Agnes Syafitri (Penerbit Jurnal Indonesia, 2026)
This study investigates the direct and indirect effects of innovation culture and organizational support on employee performance through innovative behavior within the X Department of West Java Province. Using a quantitative explanatory design, data were collected from 69 civil servant employees who had worked for at least three years. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results reveal that innovation culture, organizational support, and innovative behavior each have a positive and significant impact on employee performance. Furthermore, innovation culture significantly influences innovative behavior, while organizational support does not. The mediation analysis indicates that innovative behavior mediates the relationship between innovation culture and employee performance, but not between organizational support and employee performance. These findings highlight the importance of strengthening innovation culture within public sector organizations as a key driver for enhancing innovative behavior and improving employee performance. The study contributes to organizational behavior and human resource management literature by providing empirical evidence on the mechanisms linking innovation culture, organizational support, and performance outcomes in a public sector context.